DALITS AND THEIR CUISINE : A JOURNEY OF IDENTITY, RESILIENCE, AND CULINARY HERITAGE (International Journal of Food and Nutritional Sciences, 2022)
The Dalit concern is a by no means ending phenomenon within the Indian scenario, also the cases of atrocities and discrimination against them is in no way a new topic of discussion. This text tries to unveil the ingesting habits of dalits at some stage in the country, alongside certain interrogations about their cuisine, How is their meals related to their subculture? And so forth. For this enquiry, writings related to Dalit culture such as the autobiographies of two female dalit authors Urmila Pawar and Bama are taken into consideration. A deep look into the consuming subculture of dalits, the huge essence of caste hegemony and upper caste hindu factors can be traced.A small peep into the dalit kitchen might not create novelty but will generally tend people in general to question their own cuisine and how it got here to be. Whether the cuisine of dalits is directly or passively affected by the caste norms and barriers which are all prevalent till date, is also being analyzed.